Impact of ventilation/perfusion single-photon emission computed tomography on treatment duration of pulmonary embolism. Issue 2 (February 2015) - Begic, Amela; Opanković, Emina; Čukić, Vesna; Rustempašić, Medzida; Bašić, Amila; Miniati, Massimo; Jögi, Jonas; Bajc, Marika
<x xml:space="preserve">Abstract</x> Purpose The aim of the study was to establish whether the duration of anticoagulant (AC) therapy can be tailored, on an objective basis, by using ventilation/perfusion single-photon emission computed tomography (V/P SPECT) and to assess the extent of residual perfusion defects over time. In particular, we addressed the following: (a) is the extent of perfusion recovery at 3 months of initial pulmonary embolism (PE) diagnosis a satisfactory criterion for deciding the duration of oral AC? (b) Is it safe to withdraw AC at 3 months if perfusion recovery is complete? Patients and methods Of 269 consecutive patients with suspected PE, 100 patients were diagnosed with PE using V/P SPECT. Sixty-seven patients with acute PE were followed up clinically and with V/P SPECT at 3 months. Sixty-four patients were subject to review and examination using V/P SPECT for a period of 6 months and 33 were followed up only clinically. Therapy was terminated after 3 months if perfusion was normalized, and patients were free of symptoms and the risk of hypercoagulability. Initial extension of PE did not have an impact on decision making. Results PE extension varied from 10 to 70% in the acute stage. After 3 months, complete resolution of PE was found in 48 patients. The treating pulmonologist decided to terminate therapy in 35 (73%) patients and to continue AC in 13 patients because of persistent risk factors. Six months later, at the second control stage, 53 patients had complete recovery of pulmonary perfusion. Eleven patients still had perfusion defects at 6 months. No recurrence was identified at 6 months in the 35 patients whose therapy was terminated after 3 months. No bleeding effects were observed in any of the patients during the 6-month follow-up. Conclusion This study shows that AC therapy can be tailored, on an objective basis, by using V/P SPECT. Normalization of perfusion at 3 months of initial PE diagnosis was a reliable indicator that AC could be safely withdrawn in patients who were without hypercoagulability risk.